ERK1/2 mitogen‐activated protein kinase dimerization is essential for the regulation of cell motility - Dalia de laFuente‐Vivas; Vincenzo Cappitelli; Rocío García‐Gómez; Sara Valero‐Díaz; Camilla Amato; Javier Rodriguéz; Santiago Duro‐Sánchez; Alexander vonKriegsheim; Michael Grusch; José Lozano; Joaquín Arribas; Berta Casar; et al. (Molecular Oncology)
ERK1/2 mitogen‐activated protein kinases (ERK) are key regulators of basic cellular processes, including proliferation, survival, and migration. Upon phosphorylation, ERK becomes activated and a portion of it dimerizes. The importance of ERK activation in specific cellular events is generally well documented, but the role played by dimerization is largely unknown. Here, we demonstrate that impeding ERK dimerization precludes cellular movement by interfering with the molecular machinery that executes the rearrangements of the actin cytoskeleton. We also show that a constitutively dimeric ERK mutant can drive cell motility per se, demonstrating that ERK dimerization is both necessary and sufficient for inducing cellular migration. Importantly, we unveil that the scaffold protein kinase suppressor of Ras 1 (KSR1) is a critical element for endowing external agonists, acting through tyrosine kinase receptors, with the capacity to induce ERK dimerization and, subsequently, to unleash cellular motion. In agreement, clinical data disclose that high KSR1 expression levels correlate with greater metastatic potential and adverse evolution of mammary tumors. Overall, our results portray both ERK dimerization and KSR1 as essential factors for the regulation of cell motility and mammary tumor dissemination.